Nursing care process practice framed by transpersonal nursing care theory and predictors in Northcentral Ethiopia: mixed study design - Solomon Demis; Tigabu Munye (International Journal of Africa Nursing Sciences, 2023)
Background: The nursing care process with transpersonal humanistic nursing care is the most important emerging part of nursing care. Studies suggest that the nurses' practices in the clinical setup were not well identified in line with the caring theory perspective. Moreover, there is a limited information, in Africa including the study area.MethodAn institutional-based observational cross-sectional framed with the transpersonal nursing care theory. A census method and purposive sampling were used to select study participants. Data were checked, coded, entered, and cleaned using Epi-data version 3.1 and exported to SPSS version 20 for analysis. Binary and multivariable analyses were undertaken and p-values less than 0.05 at a 95% confidence interval were considered statistically significant. Qualitatively, the focus group discussion was audiotaped, transcribed, and formulated thematically.ResultThe overall level of nursing care process practices framed with transpersonal caring theory were found to be 11.50 % (8.5–16.0). Nurses with BSc and above [AOR = 0.32, 95% CI (0.14, 0.71)], not trained in the nursing process [AOR = 0.40, 95% CI (0.22, 0.72)], poor knowledge [AOR = 0.45, 95% CI (0.27, 0.75)], poor attitude [AOR = 0.14, 95 %CI (0.05, 0.24)], the experience of fewer than 5 years [AOR = 0.08, 95 %CI (0.04, 0.17)] were found to be inversely associated. The age group under 30 years [AOR = 3.06, 95% CI (1.63, 5.74), nurses joined nursing education by their first choice [AOR = 7, 95% CI (4.50–21.20)] and others nurses with the shorter nurse patient hours per day [AOR = 4.75, 95 %CI (2.30–11.20) were found to be positively associated with nursing process practice. The majority of Nurses' in the focus group discussion explained that nursing caring practice was limited to 'providing care for disease and patients' calling for help'.ConclusionThe level of nursing process practice was poor. Being BSc and above holders, having poor knowledge, having a poor attitude, serving for <5 years, not trained in the nursing process, and nurses age group less than 30 years, nursing as first choice and nurse-patient hours per day were found to be significantly associated with nursing care process practice. And, nurses' experience in practicing transpersonal caring as the theory was limited to 'caring for the request for help and caring for disease'. Working on knowledge, and attitude, reducing nurses' workload, educating nursing by choice in academics, and incorporating transpersonal caring theory into the practice of nurses would result in better nursing care practice.